2004
DOI: 10.1016/j.jpainsymman.2004.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer in African Americans: relationship of patient and partner self-efficacy to quality of life

Abstract: This study examined the relationship between patient and partner ratings of self-efficacy for symptom control and quality of life (QOL) among 40 African American prostate cancer survivors and their intimate partners. Data analyses revealed that cancer survivors who had rated their self-efficacy for symptom control higher reported better QOL related to urinary, bowel, and hormonal symptoms and better general health QOL (i.e., better physical functioning and better mental health). Data analyses also revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 39 publications
(38 reference statements)
10
91
1
Order By: Relevance
“…These scores are somewhat lower than those reported in a study of prostate cancer patients (range=71.1-82.9; Campbell et al, 2004) but slightly higher than those we found in a previous study of lung cancer patients (range=56.1-59.3; Porter et al, 2002). The correlation between patient and caregiver selfefficacy scores was r=.38 (p<.0001).…”
Section: Descriptive Analysescontrasting
confidence: 70%
See 2 more Smart Citations
“…These scores are somewhat lower than those reported in a study of prostate cancer patients (range=71.1-82.9; Campbell et al, 2004) but slightly higher than those we found in a previous study of lung cancer patients (range=56.1-59.3; Porter et al, 2002). The correlation between patient and caregiver selfefficacy scores was r=.38 (p<.0001).…”
Section: Descriptive Analysescontrasting
confidence: 70%
“…Cronbach alphas for the total scale score were .95 for patients and .96 for caregivers. Prior studies using this instrument to assess self-efficacy in lung cancer patients (Porter et al, 2002), prostate cancer patients and their caregivers (Campbell et al, 2004), and caregivers of cancer patients at the end of life (Keefe et al, 2003) have demonstrated evidence of internal consistency and construct validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy can affect a person's thought processes and emotions and ultimately affect his/her motivation to master the challenge presented [47]. Research in elderly post-operative patients has shown that those who had confidence in their ability to perform a given activity recovered more quickly [48].…”
Section: Review Of Literature Developmental Perspectivementioning
confidence: 99%
“…According to a recent literature review on telehealth interventions [80], a precise structure linking all aspects of the intervention or of the outcomes is rarely found and most of the projects lack a theoretical framework. Nevertheless, even in the general literature (beyond telehealth interventions) there are unfortunately only few studies which assess correlations or mediate effects between different constructs (e.g., Quality of Life, depression, self-efficacy) which are related to caregiver's needs (e.g., information provision, social support, self-management education etc) [81,82].…”
Section: Discussionmentioning
confidence: 99%